Pengaruh Value dan Parent Attachment terhadap Career Maturity berdasarkan Persepsi Mahasiswa Angkatan 2017 di Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Metro - Saputra, Irfaan Hisyam; Fitriani, Fitriani (Jurnal Manajemen DIVERSIFIKASI, 2021)
This study aims to determine whether Work Values ​​and Parent Attachments affect Career Maturity in class 2017 students at the Faculty of Economics and Business, Muhammadiyah Metro University.This type of research is quantitative. With the purposive sampling technique, namely "sampling technique with special considerations so that it deserves to be used as a sample" with a total of 113 students. Meanwhile, the data collection techniques used were questionnaires, validity tests, normality tests, linearity tests, and multiple linear regression tests with conclusions drawn through simultaneous t test and F test.The conclusion from this research is that the work value and the role of parents (parent attachment) have shown good results and have a positive and significant effect so that they can be used as references by researchers.